If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4p + -5 = 15 Reorder the terms: -5 + -4p = 15 Solving -5 + -4p = 15 Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '5' to each side of the equation. -5 + 5 + -4p = 15 + 5 Combine like terms: -5 + 5 = 0 0 + -4p = 15 + 5 -4p = 15 + 5 Combine like terms: 15 + 5 = 20 -4p = 20 Divide each side by '-4'. p = -5 Simplifying p = -5
| -16tx^2+21x-6=0 | | 6(a-8)+16=4(a-7) | | 6x-4(6-x)=2 | | Cot3x/5=-1 | | 28+36+6(-7x+c)=2(5x-6) | | 32+2x=12-7x | | 5(4x-2)+6=-3 | | 3(c-1)+4=17-(c-4) | | -8-5y-5=11-9y-16 | | -1=6-2(3y+2) | | 4x-50=4-5x | | A=x+3+z | | 4.5z=4.5z-6.25+6 | | 5x+19=x+21 | | 15-5x=-7x+15 | | 4x+16-6=22+6 | | 2y^2=13y | | 11=7+2(3z+2) | | -5x=-7+2x | | 7x+52=9x+24 | | 4m-33=11 | | 4cos^2(2t)-4sin^2(2t)=4 | | 4x-19=1x-30 | | 8z-3=-59 | | 9+(-6y)(3-y)+y^3=25 | | x^2-1=-3 | | 40x+10(1.5x)=719.47 | | 4-(2x+23)=29-8x | | 4x-1x+7x=15 | | X+2(x-9)=57 | | 3x+18=12x-27 | | 3x-12=1x-19 |